Nanocomposite electrolytic coatings based on cobalt alloys with refractory metals: obtaining, properties, application - Yar-Mukhamedova, Gulmira Shariphovna; Nenastina, Tat’yana Aleksandrovna; Ved’, Maryna Vital’yevna; Sakhnenko, Nikolay Dmitrovich; Karakurkchi, Anna Vladimirovna (Kazakh University, 2022)
Modern electrochemical technologies for surface treatment of titanium alloys to create protective, antifriction, dielectric, and catalytically active materials are considered. The physicochemical fundamentals of the processes of plasma-electro lytic formation of conversion and composite electrolytic coatings are highlighted. Separate stages of electrode reactions, regularities of the influence of electrolyte components, and electrolysis parameters on the composition, structure, and morphology of synthesized materials are examined in detail. Considerable attention is paid to improving the synthesis of multicomponent alloys and composites based on cobalt from aggregative stable and stable electrolyte solutions, and flexible control of the composition and functional properties of materials is an urgent scientific and technical problem, the solution of which is the presented study. The monograph summarizes the results of the project AP 08855457, "Development of an innovative technology for producing nanocrystalline composite coatings for fuel cell electrodes and hydrogen energy". This research has been funded by the Science Committee of the Ministry of Education and Science of the Republic of Kazakhstan. The monograph is designed for specialists in the field of chemical technology, as well as teachers, graduate students, and students of higher educational institutions.
Keywords: composite electrolytic coatings; functional materials; kinetics of cathodic processes; nano-CEC; polyligand electrolytes; photocatalytic properties; 544.6